Triple-band metasurface absorber for RF energy harvesting applications - Agrahari R.; Singh S.; Samantaray D.; Kumar B.; Bhattacharyya S.; Mahto M.; Jain P.K. (My University, 2025)
Energy harvesting is expected to be ubiquitous and essential to modern-day life in the future. The limitations of ambient sources, such as thermal, mechanical, and solar, for energy harvesting can be overcome by RF energy harvesting for low-power devices. With the help of perfect metasurface absorbers, an electromagnetic wave can be used as an ambient source for energy harvesting. In this paper, a simple polarization-insensitive triple-band perfect metasurface absorber is proposed for RF energy harvesting applications. The three-layer (metal–dielectric–metal) meta-atom of the designed metasurface consists of a cross-shaped metal patch surrounded by slotted square-shaped metallic patches and of (Formula presented.) meta-atoms. The absorber is typically developed in S- and C-bands with resonant frequencies of 3.06, 3.9, and 5.97 GHz. The absorption is near unity which persists over a wide angle of incidence. The experimental results are in close agreement, within 2%, with the simulation results. The reliability of the proposed absorber has been determined for the RF energy harvesting applications, and a high harvesting efficiency of 94.4% and 84% has been observed at 3.07 and 5.97 GHz, respectively. © 2023 Wiley Periodicals LLC.